Effectiveness of Group Play Therapy on Problematic Behaviors and Symptoms of Anxiety of Preschool Children. Issue 2 (3rd April 2019) - Swan, Karrie L.; Kaff, Marilyn; Haas, Sara
ABSTRACT: The current study explored the effects of child-centered group play therapy (CCGPT) on anxiety symptoms and problematic classroom behaviors of preschool children. Using a single case design, 4 preschool children with clinical levels of anxiety problems as rated by parents or teachers on the Child Behavior Checklist/Caregiver-Teacher Report Form, participated in 10 sessions of CCGPT. Participants' problematic classroom behaviors were examined prior to and during participation in CCGPT. After participation in group play therapy, all 4 children exhibited decreased anxiety symptoms and fewer problematic classroom behaviors. A discussion of limitations and implications for future research are discussed.